The effect of type and level of carbohydrate supplementation on intake and digestibility of Atriplex Nummularia cv. De Kock fed to sheep - Van Niekerk, Willem A. (University of Pretoria, 2013)
Dissertation (MSc Agric (Animal and Wildlife Sciences))--University of Pretoria, 2007.